2013
DOI: 10.1007/128_2013_477
|View full text |Cite
|
Sign up to set email alerts
|

CMP-Sialic Acid Synthetase: The Point of Constriction in the Sialylation Pathway

Abstract: Sialoglycoconjugates form the outermost layer of animal cells and play a crucial role in cellular communication processes. An essential step in the biosynthesis of sialylated glycoconjugates is the activation of sialic acid to the monophosphate diester CMP-sialic acid. Only the activated sugar is transported into the Golgi apparatus and serves as a substrate for the linkage-specific sialyltransferases. Interference with sugar activation abolishes sialylation and is embryonic lethal in mammals. In this chapter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 132 publications
0
30
0
Order By: Relevance
“…Previous studies revealed that divalent metals, such as Mg 2+ or Mn 2+ , are essential for the activity CMP-Sia synthetases as these metal ions bind in the vicinity of the enzyme active site and facilitate the orientation of substrates and catalysis [4]. Mg 2+ is thought to be the preferred metal cofactor for CMP-Sia synthetases, and it was used in the majority of previous studies on in vitro activities of the synthetases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies revealed that divalent metals, such as Mg 2+ or Mn 2+ , are essential for the activity CMP-Sia synthetases as these metal ions bind in the vicinity of the enzyme active site and facilitate the orientation of substrates and catalysis [4]. Mg 2+ is thought to be the preferred metal cofactor for CMP-Sia synthetases, and it was used in the majority of previous studies on in vitro activities of the synthetases.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of divalent metal cations is a strict requirement for the activity of CMP-Sia synthetase [4], including Drosophila CSAS (Fig. 4A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animals and microbes, sialic acid must be activated for use in glycan biosynthesis by conjugation with CTP, a process catalyzed by CMP-Sialic acid synthetase (Kean et al, 2004). These are encoded by the CMAS gene, which is highly conserved among vertebrates and well-conserved even in other prokaryotes and eukaryotes (Sellmeier et al, 2013). No genes with significant homology spanning the functional domains of this gene were found in C. elegans or Schistosoma genomes.…”
Section: Glycan Motifsmentioning
confidence: 99%